Programas de alimentação para fase de crescimento de duas linhagens de codornas de corte reprodutoras - Araújo, Fernanda Gabryela Bezerra de (2023)
With the aim of evaluating different feeding programs for the growth mode (14 to 42 days of age) of two lineages of breeding meat quails, 360 females and 120 males, totalizing 480 animals, were distributed in an entirely experimental design randomized in a 3x2 factorial design (three dietary programs and two strains), totaling six treatments. The feeding programs were: P1 - unlimited feeding; P2 - controlled daily feeding; P3 - daily food with 10% restriction of the food offered in P2. At 42 days of age and maintaining the experimental design, the birds were transferred to the production shed, remaining until 51 weeks of age when they received unlimited food. Performance parameters were evaluated in the growth mode, sexual maturity, breeder performance, egg quality, incubation and progeny performance. There was no interaction between the factors studied for performance parameters in the growth mode. Between the lines, there was a difference only in weight at 42 days of age. In relation to feeding programs, it was observed that birds restricted to 10% had lower feed consumption, weight gain and average weight at 42 days of age, compared to birds in other feeding programs. In sexual maturity indicators, it was verified that birds with a 10% restricted diet were four days later in producing the first egg compared to the others. In the laying phase, there was no significant effect for interaction between factors or between lines. However, birds restricted by 10% showed lower consumption during the production phase and lower body weight at the end of the experiment, while birds with unlimited food showed higher mortality during the egg production phase. For egg quality parameters, incubation and progeny performance, no interaction was observed between factors, strains and feeding programs. It is concluded that feeding program from 14 to 42 days of age, with evaluated 10% restriction, decreases the quails weight at 42 days of age, delays sexual maturity and also reduces feed consumption, mortality and body weight at the end of the laying cycle, and without compromising the (re)productive and progeny performance. Therefore, it can be recommended.